2012
DOI: 10.1371/journal.pone.0052284
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 4D Phase-Contrast MRI Flow Measurements to Computational Fluid Dynamics Simulations of Cerebrospinal Fluid Motion in the Cervical Spine

Abstract: Cerebrospinal fluid (CSF) dynamics in the cervical spinal subarachnoid space (SSS) have been thought to be important to help diagnose and assess craniospinal disorders such as Chiari I malformation (CM). In this study we obtained time-resolved three directional velocity encoded phase-contrast MRI (4D PC MRI) in three healthy volunteers and four CM patients and compared the 4D PC MRI measurements to subject-specific 3D computational fluid dynamics (CFD) simulations. The CFD simulations considered the geometry t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
107
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(123 citation statements)
references
References 49 publications
13
107
2
1
Order By: Relevance
“…It has been shown that CFD may underestimate the velocity field in rigid-wall SSS models compared to velocities observed in vivo in the SSS using 4D pcMRI [10]. Thus, pressure gradients and, consequently, LI may have been underestimated by this particular CFD methodology.…”
Section: Cth Measurement Variabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that CFD may underestimate the velocity field in rigid-wall SSS models compared to velocities observed in vivo in the SSS using 4D pcMRI [10]. Thus, pressure gradients and, consequently, LI may have been underestimated by this particular CFD methodology.…”
Section: Cth Measurement Variabilitymentioning
confidence: 99%
“…Thus, pressure gradients and, consequently, LI may have been underestimated by this particular CFD methodology. Further, bulk neural tissue displacement in the spinal cord and cerebellar tonsils throughout the cardiac cycle in the rostrocaudal direction ranging from 0 to 0.6 mm has been documented for CMI patients and healthy subjects [10,[24][25][26]29]. This data suggest that elastic elements could be added to the boundary conditions that in turn may impact the pressure and velocity fields.…”
Section: Cth Measurement Variabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Mesh sensitivity was also performed by considering three different discretization schemes, as shown in Table 2. The estimation of the relative error of the flow rate introduced by grid and time discretization was calculated at the center of the cerebral ventricles in the model, using the following formula [9]:…”
Section: Methodsmentioning
confidence: 99%
“…Although such combined studies are under extensive research, a reasonable comparison method has not yet been developed. Most of these works do either not describe in detail how the comparisons were achieved exactly or perform visual interpretation [2,3,4], whereas some other works compare velocity magnitude profiles and/or peak-velocities [5,6], linear correlation coefficients [7] or volumetric flow rates [8]. Most of these comparisons are performed on 2D planes, do not define any norm or do not consider flow properties.…”
Section: Introductionmentioning
confidence: 99%